Historical blocking: RU 2023-12-29 to 2023-12-31 (Russia) - Voidly (2023)
CRITICAL severity censorship detected in Russia. Confidence: 97%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: RU-2023-0009
Keywords: censorship; RU; censorship; critical